Prolonged pleural catheters in the management of pleural effusions due to breast cancer: Erratum - Demirhan, Ozkan; Ordu, Cetin; Toker, Alper (Journal of Thoracic Disease; Vol 6, No 5 (May 08, 2014): Journal of Thoracic Disease, 2014)
In the article that appeared on Pages 74-78 of the February 2014 Issue of the Journal of Thoracic Disease, there were errors in the authors’ affiliations.